GDF10 is related to obesity as an adipokine derived from subcutaneous adipose tissue - Song, Mi Kyung; Kim, Ji Eun; Kim, Jung Tae; Kang, Yea Eun; Han, Sun Jong; Kim, Seok Hwan; Kim, Hyun Jin; Ku, Bon Jeong; Lee, Ju Hee (Frontiers in Endocrinology, 2023)
Introduction: Adipokines are proteins that are secreted by the adipose tissue. Although they are associated with obesity-related metabolic disorders, most studies have focused on adipokines expressed by visceral adipose tissue (VAT). This study aimed to identify the adipokine potentially derived from subcutaneous adipose tissue (SAT) and its clinical significance. Methods: Samples of SAT and VAT were obtained from six adult male patients who underwent laparoscopic surgery for benign gall bladder disease. Differentially expressed genes were analyzed by subjecting the samples to RNA sequencing. The serum concentration of selected proteins according to body mass index (BMI) was analyzed in 58 individuals. Results: GDF10 showed significantly higher expression in the SAT, as per RNA sequencing (fold change = 5.8, adjusted P value = 0.009). Genes related to insulin response, glucose homeostasis, lipid homeostasis, and fatty acid metabolism were suppressed when GDF10 expression was high in SAT, as per genotype-tissue expression data. The serum GDF10 concentration was higher in participants with BMI ≥ 25 kg/m2 (n = 35, 2674 ± 441 pg/mL) than in those with BMI < 25 kg/m2 (n = 23, 2339 ± 639 pg/mL; P = 0.022). There was a positive correlation between BMI and serum GDF10 concentration (r = 0.308, P = 0.019). Conclusions: GDF10 expression was higher in SAT than in VAT. Serum GDF10 concentration was high in patients with obesity. Therefore, GDF10 could be a SAT-derived protein related to obesity.